Decompression and Enucleation of a Mandibular Radicular Cyst, Followed by Bone Regeneration and Implant-Supported Dental Restoration - M. AboulHosn; Z. Noujeim; N. Nader; A. Berberi (Case Reports in Dentistry)
Odontogenic cysts are usually treated by enucleation (cystectomy). Limited cysts (less than 5 cm) are usually managed by primary excision (total cystectomy), whereas larger ones (exceeding 5 cm) are often decompressed or marsupialized. Because it consists only of opening a much smaller surgical window, decompression is regarded as a more conservative method of treatment: this method associates the creation of an opening (window) into the cystic cavity with the suturing of a decompressing device (plastic tube or stent) at the periphery of the cyst. Apart from releasing intraluminal pressure in the pathological cavity, this procedure helps the lesion to progressively decrease in volume “with a gradual increase in bone apposition” and preserves pulp vitality and periodontal integrity of the adjacent teeth. We are reporting a case of a mandibular radicular cyst that was treated by decompression, followed by enucleation, bone reconstruction, and restoration with two osseointegrated dental implants. The cystic cavity progressively decreased in volume and increased in bone density.